System identification based approach to dynamic weighing revisited. (1st December 2016) - Niedźwiecki, Maciej; Meller, Michał; Pietrzak, Przemysław
Abstract: Dynamic weighing, i.e., weighing of objects in motion, without stopping them on the weighing platform, allows one to increase the rate of operation of automatic weighing systems, used in industrial production processes, without compromising their accuracy. Since the classical identification-based approach to dynamic weighing, based on the second-order mass–spring–damper model of the weighing system, does not yield satisfactory results when applied to conveyor belt type checkweighers, several extensions of this technique are examined. Experiments confirm that when appropriately modified the identification-based approach becomes a reliable tool for dynamic mass measurement in checkweighers. Abstract : Graphical abstract: Abstract : Highlights: Dynamic weighing, i.e., weighing of objects in motion, without stopping them on the weighing platform, allows one to increase the rate of operation of automatic weighing systems used in industrial production processes, without compromising their accuracy. Since the classical identification-based approach to dynamic weighing, based on the second-order mass–spring–damper model of the weighing system, does not yield satisfactory results when applied to conveyor belt type checkweighers, several extensions of this technique are examined. The paper describes a new dynamic weighing scheme which combines identification-based approach with signal-adaptive data prefiltering. It is shown that the new technique allows one to obtain results that not only comply with stringent metrological accuracy specifications under various operating conditions, but also guarantee satisfactory robustness margins.